A novel hybrid approach to improve the performance of the solar collector: combined effect of roughness and duct modification. Issue 4 (21st December 2022) - Kumar, Rajneesh; Kumar, Sunil; Kharub, Manjeet; Goel, Varun
ABSTRACT: The solar radiation absorbed by the solar collector extracts the thermal energy from the radiation, which further helps in space heating or drying crops. Usually, such heaters transfer has poor performance because of the low heating capacity of air. A hybrid approach (i.e. combination of duct modification with roughness) has been proposed in the present study to enhance the solar air heater (SAH) performance. The effectiveness of the heater is estimated based on thermal and hydraulic performance for a given range of flow parameters. The duct modification is achieved by rounding the corners for avoiding flow stagnation at the corners and spherical-dent are fabricated over the absorber plate for better augmentation of energy. The arrangement of these spherical dents is decided using relative transverse (Pt ) and longitudinal pitch (Pl ), while its shape is estimated using relative dent height (Hd ). With the proposed modifications, the augmentation of energy improved significantly by 378% at a low Reynolds number due to development of flow vortices near the dents in the flowfield. At low Reynolds number, the overall performance was found to be highest, that is, 2.6 in the proposed design which is higher than the rectangular and triangular passage SAH with semispherical dents. But with an increase in flow rate, the overall performance decreased to 1.4. The experimentally obtained results are also combined in the form of heat transfer and flow characteristic correlations using regression analysis summarized in a form of correlation for heat transfer and flow characteristics.